MICROBIOLOGICAL INDICATORS OF PATIENTS WITH CONFIRMED SARS-COV-2 INFECTION (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
The article presents a bacteriological analysis of patients admitted to the Bukhara Regional Infectious Diseases Hospital on March 16, 2020 to February 02, 2022 with a diagnosis of COVID-19 coronavirus infection and confirmed SARS-CoV-2 infection (a positive result of real time PCR, typical for SARS-CoV-2). The results are presented from stool samples taken from patients of Pr. Vulgaris, Pr. Mirobllis, Kl. phevmoniae, Enterobacter hafniae,, from sputum samples of St. pneumoniae, Can.viridans; St. epidermis, St. aureus were isolated from the blood sample. Most of the isolated microorganisms were sensitive to levofloxacin, amikacin, ciprofloxacin and cefaperazone sulbactam.